2021
DOI: 10.3389/fphys.2020.597429
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Matrine Protects Cardiomyocytes Against Hyperglycemic Stress by Promoting Mitofusin 2-Induced Mitochondrial Fusion

Abstract: Matrine, an active component of Sophora flavescens Ait root extracts, has been used in China for years to treat cancer and viral hepatitis. In the present study, we explored the effects of matrine on hyperglycemia-treated cardiomyocytes. Cardiomyocyte function, oxidative stress, cellular viability, and mitochondrial fusion were assessed through immunofluorescence, quantitative real-time PCR (qRT-PCR), enzyme-linked immunosorbent assays, and RNA interference. Matrine treatment suppressed hyperglycemia-induced o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, research studies revealed their impressive antimicrobial [ 6 , 8 , 177 ], antifungal [ 6 , 8 , 111 , 112 ], and antimycobacterial [ 10 , 178 ] effects, and some of them displayed activity superior or comparable to those presented by chloramphenicol [ 112 ], amphotericin B [ 115 ], and rifampin [ 124 ]—drugs used in standard therapeutic regimens. Moreover, naphthyridines were shown to present significant properties including antiinfectious: antiviral [ 11 , 24 , 50 , 51 ], antiparasitic [ 9 , 176 ], and antimalarial [ 113 ]; anticancer [ 5 , 6 , 23 , 35 ]; influencing cardiovascular system: hypotensive [ 16 , 27 ], cardioprotective [ 43 , 44 ]; neurological: sedative [ 94 ], analgesic [ 15 ], anticonvulsant [ 78 ], stimulating neuritogenesis [ 188 ]; psychotropic: antianxiety [ 97 ], antidepressant [ 29 , 97 ]; and affecting immune system: anti-inflammatory [ 7 , 56 , 57 ], immunosuppressant [ 48 , 49 , 50 ]. The spectrum of activity of naturally-derived naphthyridines is wide, thus these compounds are undeniably fascinating subjects of research.…”
Section: Discussionmentioning
confidence: 99%
“…Matrine 30 also exerted a significant effect in drug-resistant tumors by inducing apoptosis and inhibiting efflux-pump activity [ 41 , 42 ]. Beside anticancer properties, matrine 30 exerted cardioprotective effects towards cardiomyocyte damage during hyperglycemia and sepsis [ 43 , 44 ]. Moreover, matrine 30 properties of protecting liver function resulted in several clinical trials.…”
Section: Naturally Occurring Naphthyridine Derivativesmentioning
confidence: 99%
“…MT treatment inhibited the expression of two peroxisome proliferator-activated receptors (PPARβ, PPARγ1), and reduced ROS and MDA levels in cardiomyocytes of DCM rats, thus suppressing the activation of the TLR-4/MyD-88 pathway induced by oxidative stress, and decreased the expression of pro-apoptotic factors caspase-8 and caspase-3 ( 50 , 51 ). MT attenuated oxidative stress by upregulating the expression of Nrf2 and HO-1 ( 52 ). Additionally, the peroxidation reaction in DCM rat cells played a critical role in the formation of atherosclerotic plaques by mediating pathological processes in related cell types such as vascular smooth muscle cells, endothelial cells, and macrophages ( 145 ).…”
Section: Application Of Mt and Omt In Cardiovascular Diseasesmentioning
confidence: 99%
“…Furthermore, MT exerted potential anti-inflammatory effects by downregulating the TGF-β-induced PERK signaling pathway and suppressing levels of inflammatory factors TNF-α and IL-6 ( 51 ). Mitochondrial fission observed in DCM rat cardiomyocytes, which accelerated mitochondrial autophagy, was mitigated by MT through activation of Mfn2, facilitating the fusion of damaged mitochondria to preserve function ( 52 ). Furthermore, OMT, by activating the Nrf2/HO-1 pathway and inhibiting the JAK/STAT pathway, enhanced the activity of antioxidant enzymes such as glutathione, SOD, and catalase, and modulating the expression of inflammatory factors, thereby alleviating changes in blood glucose levels and left ventricular systolic pressure in type 2 diabetic rats ( 71 ).…”
Section: Application Of Mt and Omt In Cardiovascular Diseasesmentioning
confidence: 99%